A new species of African Snake-Eyed Skink (Scincidae: Panaspis) from Ethiopia - Colston, Timothy J.; Pyron, R. Alexander; Bauer, Aaron M. (Zootaxa, 2020)
A recent molecular phylogenetic revision of the snake-eyed skinks (genus Panaspis Cope, 1868) uncovered extensive cryptic diversity, including several new species from throughout sub-Saharan Africa. Here, we describe one of these from Ethiopia as Panaspis annettesabinae sp. nov. This description is based on a previous molecular phylogeny and morphological, scalation, and coloration data collected from the type specimen. Phylogenetic analyses place the species alone in what we term the P. annettesabinae species group from Ethiopia. This group forms the sister lineage to a large southern African radiation and suggests a potential northern origin for much of the extant diversity of Panaspis. Many new taxa have recently been discovered in the genus and region, and there are several historical records of Panaspis from elsewhere in Ethiopia. Thus, we suggest that the range of this new species (known only from a single specimen at present) may be much larger, and that additional undescribed species may exist in northern sub-Saharan Africa.